Newly designed plastic stent for endoscopic placement above the sphincter of Oddi in patients with malignant hilar biliary obstruction. (25th April 2013) - Ishiwatari, Hirotoshi; Hayashi, Tsuyoshi; Ono, Michihiro; Sato, Tsutomu; Kato, Junji
Abstract : Background: Plastic stent (PS) occlusion occurs as a result of bacterial adherence to the stent's inner wall. To retain the bacteriological barrier, placing a PS above the sphincter of Oddi ('inside stent') has been investigated. We designed a new PS (inside stent with thread [IT] stent) with attachable nylon thread for use as an inside stent and for easy retrieval. The present study evaluated the IT stent's technical feasibility and efficacy for malignant hilar biliary obstruction. Patients and Methods: A total of 26 consecutive patients with unresectable malignant hilar biliary obstruction underwent placement of IT stents from August 2007 to February 2011. IT stents were placed across the strictures without sphincterotomy to achieve bilateral drainage. Results: The overall technical success rate of the IT stent was 100% for one session. Multiple IT stents were inserted in 25 cases(two stents in 15 patients, three stents in 10 patients). No stent‐related early complications occurred. The functional success rate was 92% (24/26). The rate of reintervention because of stent malfunction was 50% (13/26). In all 16 patients who underwent stent removal, IT stents were easily retrieved using the nylon thread. According to Kaplan–Meier analysis, the median stent patency period was 136 days. Conclusion: IT stents for endoscopic placement above the sphincter of Oddi can be used safely and effectively for malignant hilar biliary obstruction.